2005
DOI: 10.1093/humrep/deh758
|View full text |Cite
|
Sign up to set email alerts
|

Influence of early ICSI-derived embryo sHLA-G expression on pregnancy and implantation rates: a prospective study

Abstract: PR and IR increased with the addition of each sHLA-G+ embryo, regardless of age. While there are significant barriers to routine embryo sHLA-G testing, we believe that if implemented, this would provide a mechanism for optimizing IVF PR while minimizing the risk of multiple pregnancies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
32
0
3

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 25 publications
6
32
0
3
Order By: Relevance
“…In this respect, the only biochemical marker so far proposed for the selection of the most promising embryo obtained by IVF is represented by the release of in vitro cultured embryo (24-, 48-and 72-hours embryo) of soluble HLA-G (Histocompatibility Leukocyte Antigen-G) molecules. This has been consistently reported by several groups [2][3][4][5][6][7]. Using Enzyme-Linked Immunosorbent Assay (ELISA) and Bio-plex approaches, these groups reported that high expression of soluble HLA-G is associated with higher pregnancy and implantation rates.…”
Section: Introductionsupporting
confidence: 63%
“…In this respect, the only biochemical marker so far proposed for the selection of the most promising embryo obtained by IVF is represented by the release of in vitro cultured embryo (24-, 48-and 72-hours embryo) of soluble HLA-G (Histocompatibility Leukocyte Antigen-G) molecules. This has been consistently reported by several groups [2][3][4][5][6][7]. Using Enzyme-Linked Immunosorbent Assay (ELISA) and Bio-plex approaches, these groups reported that high expression of soluble HLA-G is associated with higher pregnancy and implantation rates.…”
Section: Introductionsupporting
confidence: 63%
“…It has also been reported that soluble HLA-G secretion was independent of embryo grade, but the cleavage rate of embryos secreting soluble HLA-G was significantly higher than that of those lacking it, as was the live birth rate (9). A prospective study, in which at least one embryo known to be producing soluble HLA-G was transferred to the mother, has also shown significantly improved implantation and pregnancy rates (10).…”
Section: Discussionmentioning
confidence: 95%
“…Due to the low sHLA-G concentration in embryo cultures (EC), the HLA-G immunodetection method and sample treatment strongly determine the reliability of the sHLA-G measurement in embryo culture supernatants. Technical difficulties have led to very controversial results in the past [100,[104][105][106][107][108][109][110][111][112][113][114][115][116][117][118] but are being resolved. sHLA-G in embryo culture supernatants is mostly measured by sandwich ELISA or ALBIA (addressable laser bead immunoassay) techniques.…”
Section: Hla-g Expression In Preimplantation Embryos and Its Clinicalmentioning
confidence: 99%